Kaidah al-Yaqīn Lā Yazūlu bi al-Syak dan Penerapan dalam Mengambil Hadis Ahad: Rule of al-Yaqīn Lā Yazūlu bi al-Syak and Application in Taking Ahad Hadith - Muhamad Syafi'ie; Ahmad Syaripudin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to know and understand the rules of al-Yaqīnu Lā Yazūlu Bi al-Syak and its application in taking ahad hadith. The problems that the authors raise in this study are; First, what is the position of the Rule of al-Yaqīnu Lā Yazūlu Bi al-Syak in Islamic law. Second, how is the application of the Rule of al-Yaqīnu Lā Yazūlu Bi al-Syak in taking ahad hadith. This research uses a descriptive research type (illustration) by using the library research method (literature review) and using a normative and philosophical juridical approach. The research results found are as follows; First, the Rules of al-Yaqīnu Lā Yazūlu Bi al-Syak is one of the qawāid kubrā, where Islamic law can be applied with this Rule. The rule of al-Yaqīnu Lā Yazūlu Bi al-Syak is the basis of an essential belief, this rule is based on texts, so that it becomes a secondary source of law. The rule of al-Yaqīnu Lā Yazūlu Bi al-Syak is considered as a consideration for a mujtahid in taking law or practice, to maintain basic matters; religion, soul, reason, and belief. Second, the application of the Rule of al-Yaqīnu Lā Yazūlu Bi al-Syak in taking hadiths is seen from two sides: (1) from the point of view of true belief, namely the release of the heart from doubts. (2) in it there is a belief that returns to a mujtahid in the form of the benefits of the practice contained in the contents of the hadith ahad.